2020
DOI: 10.3390/nu12072099
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Protein Supplementation Targeted at Improving Muscle Mass on Strength in Cancer Patients: A Scoping Review

Abstract: Deterioration of muscle strength during cancer results in functional limitation, poor quality of life and reduced survival. The indirect effects on muscle strength of nutritional interventions based on protein and amino acid derivatives targeted at improving muscle mass are poorly documented. A scoping review was performed to examine the available evidence on the effects of proteins, amino acids and their derivatives on muscle strength in adult cancer patients. Pubmed and Scopus databases were searched to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Second, we did not measure muscle function parameters. While skeletal muscle mass and function are generally related, changes in one parameter following specific interventions do not necessarily predict the other, since function may be affected by altered neuromuscular signaling and muscle contractile quality [72,73]. We therefore cannot assume proportional changes occurring in muscle function and mass in the current model; skeletal muscle mass preservation has however independent clinical relevance, based on previous demonstrations that muscle mass loss per se is associated with negative outcomes in CHF patients [65] as well as other disease conditions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not measure muscle function parameters. While skeletal muscle mass and function are generally related, changes in one parameter following specific interventions do not necessarily predict the other, since function may be affected by altered neuromuscular signaling and muscle contractile quality [72,73]. We therefore cannot assume proportional changes occurring in muscle function and mass in the current model; skeletal muscle mass preservation has however independent clinical relevance, based on previous demonstrations that muscle mass loss per se is associated with negative outcomes in CHF patients [65] as well as other disease conditions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it comes as no surprise that excessive muscle loss (muscle atrophy) is an important clinical feature in many diseases such as cancer, chronic liver and lung diseases, spinal cord disease, and infections [ 2 , 3 ]. The existence of muscle stem cells endows skeletal muscle the capacity of regeneration, so stimulation of postnatal muscle regeneration has become an important strategy to treat atrophying muscle [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of protein on muscle strength is also an important consideration in cancer given that muscle weakness can occur without loss of muscle mass [31]. A review that focused on nutritional interventions for muscle strength in cancer found no studies that compared plant-with animal-based diet interventions [111]. Clinical trials related to protein source and muscle anabolism in cancer primarily focused on MPS and MPB rather than whole-body lean mass response and its impact on clinical outcomes.…”
Section: Additional Considerations and Current Evidence Of Animaland ...mentioning
confidence: 99%